Черчение в средней школе: пособие для учителей / А. Д. Ботвинников, И. С. Вышнепольский, В. Н. Виноградов ; под ред. А. Д. Ботвинникова - Ботвинников Александр Давидович (Просвещение, 1979)
Экземпляры: КХ (20121122) / Инвентарный номер: 714150 / Цена: 0.25 / Сис.шифр: 744 / Авт.знак: Б 86 / ГРНТИ: 81 / ББК: 3